Assessing the mental health impacts of COVID-19 on Healthcare Workers in South Africa: A Systematic Review - A.P, Baloyi; A, Ncube; Tlou D, Raphela (Journal of Ecohumanism, 2025)
This paper looks at the impact of COVID-19 on the mental health of healthcare workers (HCWs) in public health facilities in South Africa. The pandemic's massive caseload forced HCWs to work longer hours and multiple shifts without any breaks, frequently with fewer resources, and in questionable facilities. Methodology: The qualitative study used evidence-based bibliometrics to explore how the COVID-19 pandemic affected the mental health of HCWs in public health facilities in South Africa. A world-curated search was conducted on Google Scholar and Scopus to obtain a relevant sample of peer-reviewed journal articles from March 2020 to August 2022. Through content analysis, the research presented in this paper highlights the lived experiences of HCWs at the forefront of the COVID-19 pandemic. Study findings and conclusions: The study found five themes that emerged from the contents: 1) Perceptions of COVID-19. The HCWs did not have much knowledge of COVID-19, which brought about a lot of fear and anxiety. 2) Working experience during the COVID-19 pandemic, reports of HCWs from the studies analysed showed that the HCWs' had to work longer hours and sometimes without the required PPE to protect them from contracting the virus. 3) Mental health support from health facilities: while mental health support services were offered, not all HCWs sought assistance for various reasons. 4) How mental health support can be improved: more support was suggested in the form of fostering a culture of health and wellness because burned-out and distressed HCWs typically do not seek help. 5) Mental health impact. This study, based on the papers analysed, concludes that COVID-19 had a negative impact on the mental health of HCWs in public health facilities in South Africa. The content analysis revealed that many HCWs developed PTSD while others developed anxiety and depression.